Pelatihan Pembuatan Jerami Padi Amoniasi Untuk Mengatasi Kerisis Pakan Ternak Pada Kelompok Tani- Ternak Aqiqah Desa Sidingkat Kec. Padang Bolak, Kab. Padang Lawas Utara - Arum Chandra Kartika, Aulia; Rianita, Resti; Sari, Ricca; Hutasuhut, Ulina; Hafni, Syafrida (Journal of Social and Community Service, 2023)
The purpose of this service is to provide counseling to Aqiqah farmer groups regarding the application of rice straw waste feed processing technology to become an alternative feed for breeders during the dry season. This service activity was carried out at the Aqiqah Livestock Farmer Group in Sidingkat Village in Padang Bolak District, North Padang Lawas. The benefits obtained in community service activities are to increase farmers' knowledge about preservation technology and fermentation of feed from rice straw waste. Guidance activities for breeders are carried out in the following manner: 1) Submission of material regarding the purpose and benefits of making ammoniated rice straw. 2) Demonstration of forage preservation by fermentation. The extension was carried out on June 25, 2022. The extension activity was attended by 21 members of the Aqiqah farmer group. The manufacture of fermented feed begins with chopping rice straw, then drying the rice straw so that the water content in the rice straw is reduced by around 15-20%, then the dry rice straw is given urea liquid, the straw that has been given urea solution is then put into plastic and packaged. close tightly so that no air enters. In this fermentation process using an anaerobic system. The duration of the fermentation process is about 3 weeks or 21 days. All community service activities were enthusiastically attended by members of the Aqiqah farmer group.